S102 Lipoxin A4 Improves Efferocytosis Via Inhibition Of The Hmgb1 In Human Alveolar Macrophages. (10th November 2014) - Wang, Q; Parekh, D; D'Souza, VK; Dancer, R; Patel, JM; Bartis, D; Gao, F; Lian, Q; Jin, S; Thickett, DR
Abstract : Introduction: Effective clearance of apoptotic cells by macrophages, termed efferocytosis, is a pre-requisite for successful resolution of inflammation. High mobility group box protein 1 (HMGB1), is an alarmin that may promote inflammation as well as suppress phagocytosis. Lipoxin A4, represents one of a unique class of lipid mediators that possess a wide spectrum of anti-inflammatory and pro-resolution actions. We hypothesised that lipoxin A4 may promote both apoptosis in neutrophils, and stimulate macrophage efferocytosis, acting as an antagonist to HMGB-1. Methods: Neutrophils were obtained from healthy volunteers and cultured for 24 h with or without lipoxin A4. Apoptosis of neutrophils was determined with Annexin V/SyTox staining by flow cytometry. HMGB-1 levels in Acute Respiratory Distress Syndrome (ARDS) bronchoalveolar lavage fluid (BALF) was measured by ELISA. The effects of HMGB-1 and lipoxin A4 upon alveolar macrophage efferocytosis was assessed by measuring the ingestion of CMFDA labelled apoptotic neutrophils by flow cytometry. The PI3K (P85) protein expression was measured by western blotting. Results: Treatment of lipoxin A4 (100 nM) increased the apoptosis of neutrophils (p = 0.0244), and reduced the dead (p = 0.0238) and necrotic neutrophils (p = 0.0358) compared to control (n = 8). BALF from patients with ARDS suppressed efferocytosis of apoptotic neutrophils. The effects of BALF correlated with HMGB-1 levels in the BALF fluid. HMGB-1 decreased efferocytosis (p < 0.05) in a dose dependent manner, and reached a significant effect at 150 ng/ml (p = 0.008). Lipoxin A4 increased the efferocytosis (p < 0.05) of alveolar macrophages in a dose dependent manner, and reached the maximal effect at 100 nM (p = 0.008). Moreover, lipoxin A4 (100 nM) blocked the decreased efferocytosis response to HMGB-1 (150 ng/ml) (p = 0.005, n = 8). The lipoxin A4 beneficial effects were abrogated by ALX antagonist, BOC-2 (p < 0.05) and PI3K inhibitor (p < 0.05). Conclusions: Lipxin A4 in vitro promotes the apoptosis but not necrosis of neutrophils. In tandem it stimulates efferocytosis of alveolar macrophages. Elevated HMGB-1 in ARDS BALF suppresses efferocytosis. Lipoxin A4 can block these effects of HMGB-1. The effect of lipoxin A4 increasing efferocytosis was through ALX–PI3K signalling pathways. Lipoxin A4 may therefore have potential as a therapeutic agent to promote the resolution of neutrophilic inflammation in ARDS.